2011
DOI: 10.1063/1.3564885
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of ferroelectric field effect transistor based on sustainable strongly correlated (Fe,Zn)3O4 oxide semiconductor and their electrical transport properties

Abstract: We have constructed a field effect transistor structure composed of the sustainable oxide semiconductor ͑Fe, Zn͒ 3 O 4 with high Curie temperature and ferroelectric Pb͑Zr, Ti͒O 3 . Electric field control of ͑Fe 2.5 Zn 0.5 ͒O 4 channel resistance was achieved in the heterostructures though modulation of their carrier concentration. The results will lead to the significant development of sustainable oxide semiconductor spintronics devices working at room temperature.Field effect control of transition metal oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…(Fe,Zn) 3 O 4 (FZO) is a promising candidate for its integration with BFO due to his high oxidative resistance. It is also a carrier-tunable magnetic semiconductor [9] with a high Curie temperature above room temperature [10]. C-AFM technique has already been proven to be useful for the characterization of this material such as FZO nanodots [11].…”
Section: Introductionmentioning
confidence: 99%
“…(Fe,Zn) 3 O 4 (FZO) is a promising candidate for its integration with BFO due to his high oxidative resistance. It is also a carrier-tunable magnetic semiconductor [9] with a high Curie temperature above room temperature [10]. C-AFM technique has already been proven to be useful for the characterization of this material such as FZO nanodots [11].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal oxides display attractive spin-related electronic properties such as high Curie temperature, possible perfect spin-polarization, and colossal magnetoresistance, and much attention has been paid to the use of the respective heterostructures as ferromagnetic field-effect transistors, [1][2][3][4] diodes, 5) and tunneling magnetoresistance devices. 6) A recent breakthrough in oxide nanofabrication techniques has been reported by Zheng et al: 7) the selfassembled growth of nanoscaled heterojunctions typically involving nanocomposite structures of perovskite BaTiO 3spinel CoFe 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with Fe 3 O 4 , partially Znsubstituted Fe 3 O 4 , namely (Fe,Zn) 3 O 4 , has high oxidative resistance and is a carrier-tunable magnetic semiconductor with a high Curie temperature above room temperature. 2,15) In this research, we have tried to obtain nanocomposite thin films comprising the (Fe,Zn) 3 O 4 (FZO) and ferroelectric BiFeO 3 (BFO) by the self-assembled growth method, and successfully obtained nano-composite oxide thin films with spintronic materials.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, by fabricating a ferroelectric Pb(Zr,Ti)O 3 bottom-gate FET, we controlled the conductivity of a Zn-substituted Fe 3 O 4 (Fe 2:5 Zn 0:5 O 4 ) film. 12) The field-effect mobility FE was, however, found to be very low, 8:1 Â 10 À4 cm 2 V À1 s À1 ; carriers doped by the field effect only slightly modified the channel conductivity. During the course of optimizing the device structure, we found that the lattice mismatch between Fe 2:5 Zn 0:5 O 4 (lattice constant: a A) with a mismatch of $8% showed one order of magnitude lower conductivity than a film prepared on a lattice-matched MgO(001) substrate (2a MgO ¼ 8:422 A).…”
mentioning
confidence: 96%
“…The device exhibited typical n-type behavior, as reported previously for Fe 2:5 Zn 0:5 O 4 /Pb(Zr,Ti)O 3 devices. 12) Figure 3(a) displays the dependence of the drain-source current I D on the gate voltage V G measured for a sample with W ¼ 30 m. V G was applied such that the gate leakage current did not exceed 0.2 nA, while the drain-source voltage V D was fixed at 10 V. The application of a positive (negative) V G induces the accumulation (exhaustion) of electrons at the surface of Fe 2:5 Zn 0:5 O 4 , resulting in an increase (a decrease) in I D , i.e., conductivity. From the slope of the I D -V G curve, FE was estimated to be 1:2 Â 10 À2 cm 2 V À1 s À1 using the general relation,…”
mentioning
confidence: 99%